Dubbing Almanya. (Multilingual) Musical Intertextuality and Literary Solidarity in Duygu Agal's "Yeni Yeserenler" - Duncan Gullick Lien (Undercurrents)
Building on Anna Kornbluh’s characterization of literary form as a key symbolic infrastructure for solidarity, this article studies the role of musical intertexts in literary expressions of solidarity. In analyzing Duygu Agal’s Yeni Yeserenler (The Newly Sprouted 2022), I focus on the formal stakes of musical lyrics as epigraphs and allusions to music in the text itself. I relate these features to the novel’s themes of racism and queer self-actualization. It is in this context that Agal proposes solidarity that transcends the (Turkish-)German context through musical references in the text.